Librarians’ Use of Social Media for Professional Development in Nigeria - Onuoha, Uloma Doris (Information Management and Business Review, 2013)
This paper examined the use of social media for professional development by librarians in Nigeria. The study was carried out using the survey research method. The study population was made up of 1294 registered members of Nigerian Library Association Online Forum. Random sampling technique was used in selecting 297 respondents for the study. Data was collected by means of questionnaire. Findings from the study revealed that online discussion forums such as NLA online forum, online social networks such as Facebook and Wikis were mostly used for professional development, while others such as podcast and book marking tools were used minimally. Librarians were also found to learn mostly by reading through the conversations of others and joining discussion groups. Based on the findings, the study concluded that librarians in Nigeria actively seek means of professional development using social media and recommends among others, that the use of social media applications such as podcast and bookmarking tools be explored as they could also contribute to professional learning/development.